Effects of the particle size and temperature on the efficiency of nanofluids using molecular dynamic simulation. (2nd May 2016) - Lee, S. L.; Saidur, R.; Sabri, M. F. M.; Min, T. K.
ABSTRACT: Nanofluids are conventional heat transfer fluids with suspended nanoparticles to enhance their thermal conductivity. However, enhancement of thermal conductivity is coupled with increased viscosity. This study investigates the efficiency of nanofluids (ratio of thermal conductivity and viscosity enhancement) with the effects of particle size and temperature using molecular dynamic (MD) simulation. The efficiency of nanofluids is improved by increasing particle size and temperature. The thermal conductivity enhancement increases with increasing particle size, but is independent of temperature; the viscosity enhancement decreases with increasing particle size and temperature. Particle size variation is therefore shown to be more effective than temperature control.